KEADAAN SANITASI HOTEL MElATI SINGARAJA INDAH DAN GRIYO MUlYO SURABAYA TAHUN 2012 - Fitri Ros Santi; Suparlan .; Khambali . (GEMA LINGKUNGAN KESEHATAN, 2013)
Melati is one type of hotel frequented by a lot of consumers since they are affordable by communitiesespecially the middle class, local or international. In their operational activities hotels that provide facilitiesshould be supervised regularly. Impairments with regard to health standard may support transmission ofdiseasesamong guests and to and from hotel employees.The study took place at the Hotel Melati Singaraja Indah and Griyo Mulyo within the operationall areaof PuskesmasPenelehSurabaya. This descriptive research aimed to describe objectively the sanitary conditionof such an establishment such as the exterior and interior environment in a hotel building; sanitary facilities,and facilities for hotel employees. Researchwas carried out upon the lodging component of the hotel, usingpredetermined criteria in an appraisal scoring system. Data were gathered by means of observation,interviews, measurement of several quality parameter of the physical environment and assessment ofsecondary data records.The results showed that sanitary condition of Hotel Melati Singaraja Indah and Griyo Mulyo Surabayawere satisfactory, having a total score of 1099 ( 86 % ).Reviewing all variables assessment of lodging sanitation there are several health requirements whichhave not been satisfied, such as : hotel surroundings, there was no efforts in preventing infestation of insectsand pests due to open garbage containers located in outer courtyard, resting quarters for employees arecomfortable and but there was no separation between male and female employee,there is a need foradditional shower and toilet facilities for employees. Linens should be stored in closed cabinets andwarehouses should be kept neat and clean.Among the suggestions are the provisions of covers for existing garbage containerslocated outside inthe hotel courtyard to prevent rodents and cockroaches harborage; provision of closed cabinet for storinglinens, improvement of cleanliness and managing the goods warehouses, provision of comfortable and saferesting quarters for employees.Classification: The state of sanitation, sanitary facilities, hotel melati